Filtration of palm oil milling effluent - Mohd Zikeri, Muhammad Zharith (2017)
The palm oil mill effluent is a waste produced by the palm oil milling activities. It consists of high amount of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), turbidity, suspended particles, color, and heavy metal content. Currently, the POME cannot be released to the public as it will affect nature strongly. On the other hand, kenaf is a plant which is known for its mechanical properties, specifically in rope, pulp and paper. Its adsorption properties has people taken notice, and it is being further studied in various fields. One of which is the adsorption properties towards POME. The POME is divided into two, which has different pH (the source of the POME was taken is the same, where one part of the POME is inserted with an acid, in order to change its pH), to also test whether the alteration in pH has an effect on the ability of kenaf filter. The filtration process (which involves the kenaf filter; that has already being shaped into a proper form of filter) takes place for about 25 minutes before the samples are sent to be tested for suspended solids, color, BOD, turbidity, particle size and heavy metal. In the end of the research, it is found that the POME with the pH of 6 increases the adsorption ability of kenaf filter in all test but the heavy metal test.